RELIABILITY OF AN EYE-FOOT REACTION TIME TEST IN CHRONOJUMP- BOSCOSYSTEM - Jeffrey C. Pagaduan (Sport Scientific And Practical Aspects, 2025)
The purpose of this study was to determine the absolute and relative reliability as well as usefulness of an eye-foot reaction (EF RT) test using the Chronojump-Boscosystem. The study was participated by 7 college male (age: 20.0 ± 1.85 yrs; height: 170.4 ± 9.75 cm; weight: 60.7 ± 11.6 yrs; %bodyfat: 7.70 ± 2.87) and 18 female (age: 18.7 ± 1.47 yrs; height: 159.0 ± 4.11 cm; weight: 54.9 ± 10.5 kg; % bodyfat: 22.7 ± 6.11) university physical education students. They underwent right and left EF-RT test for 2 sets. Each set consists of 3 random trials completed within 30 seconds. Absolute reliability was determined using typical error as %CV. Relative reliability was identified using intraclass correlation coefficient (ICC). Test usefulness was established using smallest worthwhile change (SWC). Results revealed that EF RT on right foot showed a %CV = 0.00, ICC = 0.74 and SWC = 0.00. On the other hand, left EF RT posted a %CV =0.00, ICC = 0.86 and SWC = 0.00. In conclusion EF RT test in Chronojump-Boscosystem demonstrated good absolute reliability for right and left foot. Relative reliability for right EF RT was poor while left EF RT was good. For test usefulness, both right and left EF RT suggested marginal utility.